1998
DOI: 10.1097/00000658-199804000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Thyroid Cancer: Determinants of Disease Progression in Patients <21 Years of Age at Diagnosis

Abstract: The progression-free survival rate was better after a complete resection and in older patients. Progression-free survival rate was the same after lobectomy or more extensive thyroid procedures, but comparison was confounded by the increased use of total or subtotal thyroidectomy in patients with advanced disease. The risk of permanent hypocalcemia increased when total or subtotal thyroidectomy was done. Thyroid lobectomy alone may be appropriate for patients with small localized lesions while total or subtotal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
114
2
10

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(137 citation statements)
references
References 29 publications
11
114
2
10
Order By: Relevance
“…No patients died of thyroid cancer. Previous studies, including prior data from our institution, have demonstrated worse PFS in younger patients, those with positive margins, and patients with more advanced disease (5,6). Extent of disease, age, sex, and positive margins had no significant effect on PFS.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…No patients died of thyroid cancer. Previous studies, including prior data from our institution, have demonstrated worse PFS in younger patients, those with positive margins, and patients with more advanced disease (5,6). Extent of disease, age, sex, and positive margins had no significant effect on PFS.…”
Section: Discussionmentioning
confidence: 57%
“…Surgical removal of the thyroid is performed on nearly all patients, however, cervical lymphadenectomy and postoperative treatment with 131 I are variably used (4)(5)(6)(7). Posttreatment surveillance guidelines are not standardized, although it is known that these patients are at risk of recurrence for decades after diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…As outras foram submetidas a biópsia excisional. A histologia mostrou um total de quatro carcinomas papilíferos e dois carcinomas foliculares; esta maior incidência de carcinoma papilífero também é registrada por outros autores [1][2][3][4][7][8][9] .…”
Section: Discussionunclassified
“…Defensores da tireoidectomia total justificam este procedimento com a alta incidência de doença multifocal, sendo encontrado em 40% dos casos 8 . Estudos mostram melhor evolução após ressecção completa e em pacientes mais velhos 9 , havendo até 60% de recidiva em menores de 7 anos, contra 27% em maiores 8 . As seis pacientes estudadas foram submetidas a tireoidectomia total, sem nenhuma complicação pós-operatória, seguida de reposição hormonal com tiroxina para manter TSH entre 0,05 e 0,1mcU/ml.…”
Section: Discussionunclassified
See 1 more Smart Citation